1993
DOI: 10.1080/00288233.1993.10427494
|View full text |Cite
|
Sign up to set email alerts
|

Direct and correlated responses to selection for high or low ultrasonic backfat in depth in Southdown sheep

Abstract: Direct selection for high or low liveweight-adjusted backfat depth (LABF), assessed by ultrasound at Position C over the longissimus dorsi muscle at the last rib, in Southdown sheep resulted in highly significant differences (3.7 versus 2.0 mm at 33 kg liveweight for rams, P < 0.01) between the lines after 8 years of selection. The response to selection per unit of cumulative selection differential was generally high and apparently linear. A generation interval of 3.01 years was estimated resulting in c. 2.7 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The direct heritabilities for weight traits reported here tend to be similar to the (usually total) heritabilities for equivalent weights in meat or dualpurpose breeds reported elsewhere. The direct heritabilities for ultrasonic measurements reported are substantially higher than most other published estimates of total heritabilities (Solis-Ramirez et al, 1993;Fogarty, 1995;Morris et al, 1997;Conington et al, 1998). This result is in line with the general trend for heritability estimates to increase when more comprehensive genetic models are used.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The direct heritabilities for weight traits reported here tend to be similar to the (usually total) heritabilities for equivalent weights in meat or dualpurpose breeds reported elsewhere. The direct heritabilities for ultrasonic measurements reported are substantially higher than most other published estimates of total heritabilities (Solis-Ramirez et al, 1993;Fogarty, 1995;Morris et al, 1997;Conington et al, 1998). This result is in line with the general trend for heritability estimates to increase when more comprehensive genetic models are used.…”
Section: Discussionsupporting
confidence: 81%
“…Experimental sheep lines selected for various carcass composition traits have been established in a number of locations, particularly New Zealand and the UK (see reviews of Simm (1992 and1994)). The earlier New Zealand experiments involved selection for divergent liveweight-adjusted ultrasonic backfat depth (McEwan et al, 1989;Solis-Ramirez et al, 1993;Morris et al, 1997). Similarly, two UK experiments involved selection on an index designed to alter body composition at a constant live weight (Cameron and Bracken, 1992;Bishop, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the genetic association between bone shape and fatness for these lines is close or whether it has been a chance occurrence. It is relevant to note that withers height differences between these lines did not change appreciably over a period of several generations when differences in fatness increased significantly (Solis-Ramirez et al 1993). Pigs selected for low backfat depth have also been shown to have longer carcasses and heavier bones relative to high-backfat pigs of the same carcass weight (Mersmann et al 1984), but it is not clear whether bone shapes were different.…”
Section: Femur Shapementioning
confidence: 99%
“…Hypodermic needle measures on live animals are a relatively low cost method, which can give information on carcass traits for further inclusion in genetic evaluation programmes. Solisramirez et al (1993) have found that selection for changed body composition resulted in correlated anatomical changes. Selection programmes including live weight-or age adjusted needle and ultrasound measurements have shown to give high responses in lean growth (Ramsey et al, 1991;Simm et al, 2002;Larsgard and Kolstad, 2003;Kvame and Vangen, 2007).…”
Section: Introductionmentioning
confidence: 99%